2010
DOI: 10.1097/ijg.0b013e3181bdb570
|View full text |Cite
|
Sign up to set email alerts
|

Systemic High-sensitivity C-reactive Protein Level in Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma

Abstract: Our findings indicated no difference in the hsCRP level between XFS, XFG, and controls. This study suggests that CRP is not a predictive marker of inflammation and peripheral endothelial dysfunction in XFS, which is accepted as a systemic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
1
4
2
Order By: Relevance
“…29 In a study by Yuksel et al, serum creatinine levels of patients with PEX and control groups were reported to be similar. 30 In our study, no statistically significant difference was observed between biochemical data obtained from patients with PEX and the control group.…”
Section: Discussioncontrasting
confidence: 44%
“…29 In a study by Yuksel et al, serum creatinine levels of patients with PEX and control groups were reported to be similar. 30 In our study, no statistically significant difference was observed between biochemical data obtained from patients with PEX and the control group.…”
Section: Discussioncontrasting
confidence: 44%
“…13 In contrast, high-sensitivity C-reactive protein had not been found as a predictive marker of inflammation and peripheral endothelial dysfunction in PEXS and PEXG. 14 The inflammation is an important component of other ocular diseases such as age-related macular degeneration (AMD) and vascular diseases of retina. [15][16][17] The relationship between NLR and diabetic retinopathy was shown.…”
Section: Discussionmentioning
confidence: 99%
“…88,89 However, there are conflicting results for high sensitivity C-reactive protein. 90,91 In addition, the XFS gene sets are enriched for genes that map to variants implicated in coffee and caffeine intake. Effects of caffeine consumption in the etiology of XFS have been studied, on the premise that coffee consumption increases plasma homocysteine levels that are speculated to enhance XFS material formation by contributing to vascular damage, oxidative stress, and extracellular matrix alterations.…”
Section: Discussionmentioning
confidence: 99%